Developing Business Models as per Islamic Practices - Arshi Naim (Scholars Digest Publishing, 2022)
In the current scenario buisesses are facing many challenges for their growth and development and this problem has increased for the firms who are following a particular religious framework. This research paper deals with the business models applied in Islamic pattern of businesses, their advantages and challenges. Managing an organization is not an easy task and globally operated organizations are faced with numerous challenges. How corporate leaders should approach their obligations is one of the important queries at the desk of business researchers. This paper provides Islamic business management model; where strategic managers follow the rules of Islam in developing the strategies, learn from the authentic references for doing the Islamic way of business and accepting the outcomes without any manipulations. Surrendering to ‘divine’ instructions inculcates humility, responsibility and self-accountability among Strategic managers are required to fulfill their duties at their best. Holistic approach to organizational business management provides corporate leaders with more options to deal with issues innovatively. This article concludes that Islamic business management model is flexible enough to adapt according to the circumstances for maximum outcome of the organization that benefit the entire community without any discrimination on the bases of religion.